Rheology 1980
DOI: 10.1007/978-1-4684-3743-0_50
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Extensional Rheometry to Establish Operating Parameters for Stretching Processes

Abstract: SynopsisThis work describes a method of determining the limits of uniform extensibility, in terms of failure and fracture, from rheological tests in extensional flow. The limit of uniform stretching can be expressed in terms of the Weissenberg number for the process, as demonstrated by data for three chemically diverse polymers, polystyrene, poly(methy1 methacrylate), and a polyester. The BKZK model can be used to predict necking failure, as determined by the Considere criterion, and an empirical correlation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…However the result is changed by the introduction of chain branching as we shall see in the following section. Moreover, tests have shown that a number of common polymeric materials do indeed show elastic instability at low Hencky strains[17]. It must be remembered that the above result is obtained for the limit of infinite Deborah numbers.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…However the result is changed by the introduction of chain branching as we shall see in the following section. Moreover, tests have shown that a number of common polymeric materials do indeed show elastic instability at low Hencky strains[17]. It must be remembered that the above result is obtained for the limit of infinite Deborah numbers.…”
mentioning
confidence: 66%
“…Coggswell & Moore appear to have been the first to apply the analysis to polymer melts in the rubbery state, apparently as the result of a suggestion by J. R. A. Pearson [16]. Connelly and Pearson [17] subsequently used the analysis together with an integral constitutive equation of the K-BKZ type to quantify the transient extensional stress growth and ultimate strainto-failure of several diverse polymer melt specimens. Their results and other experimental observations are summarized in the review of Malkin & Petrie [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, insufficient measurements are reported in the literature for firm conclusions to be drawn. For instance, tensile tests on some commercial grades of PMMA and polystyrene melts show that the failure strain is independent of strain rate [27]. Fundamental models on the dependence of failure strain upon molecular weight (distribution) in the rubbery state also appear to be lacking [28,29].…”
Section: Failure Strainmentioning
confidence: 99%
“…The FENE network over-predicts the magnitude of the strain-hardening growth in the normal stress difference that occurs just before the sample ruptures, while the modified network model gives more reasonable stress growth functions. The fact that the point of rupture occurs extremely close to the finite extensibility plateau should not be surprising, since the mass rupturing of network junctions dramatically reduces the rate of stress growth in the system and can lead to tearing or necking as implied in the Considère criterion [Considère (1885); Pearson and Connelly (1982); McKinley and Hassager (1999); Ng et al (2006)]. …”
Section: E Comparison With Other Non-linear Deformationsmentioning
confidence: 99%